Efficiency of radiofrequency ablation of pulmonary vein ostium for patients with atrial fibrillation and metabolics - E. L. Zaslavskaya; V. A. Ionin; O. V. Listopad; S. E. Nifontov; K. N. Malikov; A. V. Soboleva; E. I. Baranova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The aim of this study is determination of predictors of efficiency of radiofrequency ablation (RFA) in patients with atrial fibrillation (AF) and metabolic syndrome (MS). Material and methods. 98 patients with AF (78 patients with AF and MS (IDF, 2005) and 20 patients without MS) have been examined. Comparison groups included 50 patients with MS without arrhythmia and 50 practically healthy subjects. RFA was performed with Carto 3 navigation system. Follow-up period after RFA was 12 months. Epicardial fat thickness (EFT) was measured with help of echo-cardiography. Results: patients with AF relapse had more MS components than those with effective procedure (3.21±1.18 and 1.73±1.14, accordingly, p<0.001). Initially, EFT of patients with AF relapse after RFA was larger that in patients without arrhythmia after exposure. EFT in patients with AF more than3.5 mmincreases probability of arrhythmia relapse in 1.87 times (OR: 1.87, 95 % CI 1.03 — 3.41, р = 0.04). Conclusion: determination of EFT with echo-cardiogaphy can be used in estimation of AF relapse risk after RFA.